Dinamika Lembaga Dakwah di Era Digital: Telaah Filosofis terhadap Konsep Dasar, Fungsi, dan Transformasinya - Imam Fatkhullah; Muhammad Firdaus; M. Yakub (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The digital era has significantly transformed the landscape of da’wah institutions, particularly in patterns of religious communication, institutional structures, and the construction of religious authority. These changes demand not only technical adaptation but also a philosophical and conceptual reconstruction of da’wah institutions within contemporary society. Employing a qualitative library research approach, this study analyzes relevant literature through content analysis and a critical-reflective perspective. The findings reveal a transition of da’wah institutions from normative and conventional models toward transformative, adaptive, and digitally integrated ecosystems. Ontologically, da’wah institutions function as agents of social transformation; epistemologically, they operate as integrative systems of knowledge; and axiologically, they serve as guardians of ethical and moral values in the digital sphere. The integration of Islamic values with digital innovation emerges as an essential foundation for sustaining institutional relevance, legitimacy, and credibility. Consequently, the reconstruction of the conceptual framework of da’wah institutions constitutes a strategic response to the challenges and opportunities presented by digital transformation.